An Analysis of the Impact of Heat Pump Systems on Load Matching and Grid Interaction in the Canadian Context. (November 2015) - Tamasauskas, Justin; Candanedo, José; Kegel, Martin
Abstract: This paper presents an examination of heat pump systems in single family Canadian homes from a load matching and grid interaction perspective. First, a detailed energy model of a high performance single family home equipped with a PV array is developed for two Canadian regions (Toronto and Vancouver). This energy model then serves as a base for three distinct heat pump systems, ranging from a conventional air-source heat pump to a ground-source heat pump with limited thermal storage capacity. Results are examined both in terms of the HVAC system and the total performance of the home in order to fully describe the potential impact of heat pumps as a means of improving the building/grid interaction.